A narrative understanding of the maternal experience of urban black South African mothers. - Dale, Lindsay Kate (My University, 2013)
This qualitative study explores the maternal experiences of black South African mothers living in a township in Johannesburg. Extensive research and literature has begun to address the experiences of motherhood from the mother’s perspective, however research into the experiences of black mothers is still limited. In the past psychological literature on South African motherhood tended to focus on at-risk mothers and children rather than exploring their personal narratives. This study presents the narratives of six black mothers living in Alexandra township in Johannesburg, Gauteng. The six mothers participated in individual, semi-structured interviews. The data was analysed using the narrative analysis technique. The analysis provides insight into the personal experiences of motherhood and highlights the central narratives that these mothers told. What emerged is that mothers have individual and unique stories to tell, their stories about becoming a mother are central to their narratives on motherhood and the context in which mothers mother is pivotal in shaping their mothering experiences.
Keywords: Motherhood--South Africa.; Women, Black--South Africa.